ANALYSIS OF THE INFLUENCE OF WORLD OIL PRICES, WORLD GOLD PRICES, AND THE DOW JONES INDEX ON THE COMPOSITE STOCK PRICE INDEX IN INDONESIA - A. Mahendra; Witya Shalini; Mutiara Pulungan; Abdul Haris; Syarifuddin Hz Nasution (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine the effect of World Oil Prices, World Gold Prices, and the Dow Jones Index on Indonesia's Composite Stock Price Index. The population in this study is Indonesia, and 25 of them were selected as samples of this study through purposive sampling techniques. Estimation is done by multiple regression analysis. The data used in this study are secondary data consisting of World Oil Prices, World Gold Prices, and the Dow Jones Index on the Composite Stock Price Index in Indonesia in 2000-2024. The results of this study indicate that, based on the partial test (t-test), World Oil Prices, World Gold Prices, and the Dow Jones Index significantly affect the Composite Stock Price Index variable in Indonesia. In contrast, the simultaneous test (F-test) of World Oil Prices, World Gold Prices, and the Dow Jones Index simultaneously significantly affects the Composite Stock Price Index variable.